PERANCANGAN SDLB 1 MUARA TEWEH DENGAN ASAS AKSEBILITAS - Dwijayanti, Tunjung; Dahliani, Dahliani (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Special Education Needs (SEN) or SLB for children with special needs must be able to provide an adequate and accessible environment to increase independence and support all student potential and activities. Especially in the early phase of education (elementary level) which is the initial phase for students in adapting to a new environment that still has a low level of independence. In North Barito Regency, SLB Negeri 1 Muara Teweh 1 was established which serves 4 types of students with disabilities. Judging from the standard of facilities and infrastructure in Permendiknas, SLBN 1 Muara Teweh does not meet the facility standards for an educational institution. The built physical environment both in terms of buildings and sites is not accessible. Therefore this design is intended to provide an ideal and accessible school design description for 4 types of disabilities with special needs. The concept initiated to solve design problems is 'Accessible Design'. This concept will refer to the Universal Design Principles which are realized using the Behavioral Architecture method. With this concept and method it is expected to be a solution to design problems.